Flora briofítica de las ciudades de Toro y Benavente (Zamora, España) - Ron, Eugenia; Soria, Alicia; Ballesteros, Teresa; Gómez , David; Fernández, Fernando (Botanica Complutensis, 2008)
We present the bryofloristic study of two Spanish towns, Toro and Benavente in Zamora province with a catalogue of 32 species. Eurhynchium pumilum, Scleropodium touretii and Tortella nitida, are reported as urban bryophytes for the first time. The ecology and the urban habitat where the bryophytes were collected are discussed.
Keywords: Urban bryophytes; Spanish towns